Les archives à l’épreuve du temps : les recadrements temporels des courts métrages de la série Souvenir - Huberman, Isabella (Canadian Journal of Film Studies, 2020)
This article examines how “colonial time” is called into question in two short films of the National Film Board of Canada’s series Souvenir, from 2015. The question of time lies at the heart of this series, for which the NFB commissioned contemporary Indigenous filmmakers to take up their archives of visual material on Indigenous peoples. The colonial temporal framework is at work in the vast archives of ethnographic and documentary film and photography on Indigenous peoples dating back to the early twentieth century, in which Indigenous people are often represented as part of “vanishing” cultures. Thus, in this article, I underscore the temporal interruptions that occur when ethnographic visual material of Indigenous peoples is put into the hands of contemporary Indigenous artists. I focus first on what it means to repurpose dehumanizing colonial archives and ask whether visual sovereignty is in fact possible within the archives. By analyzing the reappropriation of archival footage in the short films Mobilize by Caroline Monnet and Etlinisigu’niet (Bleed Down) by Jeff Barnaby, I elucidate how the filmmakers break with modes of colonial time through what I propose to call “reframings” that offer alternative ways of conceiving of time. By rehabilitating ethnographic images, these filmmakers refuse to project the material into the distant past and complicate the readability of Indigenous images in the archives, revealing how the reappropriation of old images can be just as powerful as the production of new ones.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

From Great-Grandmothers to Great-Granddaughters: "Moving Life" in Baby Carriers and Birchbark Baskets - Kahsenni:io Nahwegahbow, Alexandra (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Les porte-bébés et les paniers d'écorce autochtones sont, en tant que réceptacles, conçus pour porter et tenir. Outre cette fonction, ils sont aussi détenteurs d'histoires, de mémoire, et de liens familiaux. Créés individuellement et ornementés avec soin, ces objets constituent une sorte de portrait des femmes qui les ont produits, ainsi que des générations qui ont hérité des pratiques et des motifs servant à les fabriquer. En élargissant la définition de la notion de portrait de famille, cet article considère deux objets provenant de Bear Island, en Ontario. Le premier est un porte-bébé ayant appartenu à Madeline Katt Theriault, et le deuxième est un panier d'écorce vraisemblablement créé parson arrière-grand-mère Angele Katt. Par leur parenté, ces réceptacles englobent une histoire multigénérationnelle qui s'étend de l'arrière-grand-mère à son arrière-petite-fille
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Les arts wendats au service de la diplomatie et de la traite - de Stecher, Annette (Recherches amérindiennes au Québec, 2014)
Cet article porte sur les oeuvres artisanales des femmes wendates du xix ₑ siècle dans le contexte plus large des traditions des arts visuels wendats. En plus des objets commerciaux, l’auteure présente des objets faits pour être utilisés lors d’occasions cérémonielles et rituelles spéciales, et qui avaient aussi une valeur importante dans la communauté. Ces deux catégories d’artisanat dévoilent la façon dont les femmes wendates adaptaient leurs traditions artistiques aux sphères économiques et diplomatiques du monde colonial, et ce avec grand succès. Ces arts ont aidé la communauté à conserver une vision du monde amérindienne et ont préservé des traditions culturelles qui se sont perpétuées d’une génération à l’autre, tout en intégrant des innovations créatives. Ils démontrent aussi le rôle diplomatique important joué par les oeuvres présentées aux dignitaires eurocanadiens et européens dans un contexte cérémoniel, afin d’établir et de maintenir des relations politiques et économiques harmonieuses.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

The Art of Community - de Stecher, Annette (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
La nation huronne-wendat de Wendake (Lorette, Québec) a maintenu sa culture et son identité pendant des siècles, souvent en dépit de, et en résistance contre les pressions occasionnées par la présence missionnaire et les politiques coloniales. Cette survivance est tributaire de savoirs, de valeurs et de coutumes transmis de génération en génération. Cet article explore l'art de la communauté wendat et ses éléments constitutifs : la fabrication d'objets, la tradition orale, l'engagement actif des membres de la collectivité dans les pratiques traditionnelles, ainsi que l'adaptation des pratiques ancestrales aux préoccupations actuelles. Il montre comment la production artistique wendat, dans sa force expressive, contribue à la continuité et cohésion sociale de la nation wendat.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Anthem: perspectives on home and native land - Rice, Ryan (Carleton University Art Gallery = Galerie d'art de l'Université Carleton, 2008)
Eight artists from across Canada create works identify varying forms of nationhood that either serve or detract from the concept of a national accord. Each artist explores the idea of ₃anthem₄ through a wide-angle lens, broadening the national discourse to include not only colonial histories, but also distinctive and multicultural liberties that take various forms: treaties, blood, languages, sexual orientation, faith, and oral traditions. The dynamic range of art works exhibited contribute to a more inclusive national narrative and expose and accept the diverse forms of nationalism that exist across the country.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Kwah í:ken tsi Iroquois - Rice, Ryan (Ottawa Art Gallery = Galerie d'art d'Ottawa, 2008)
Catalogue d'exposition avec des textes de Ryan Rice, Françoise Charron, Emily Falvey et Hilda Nicholae.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Hochelaga revisité = Hochelaga revisited - Rice, Ryan (MAI (Montréal, arts interculturels), 2009)
Catalogue d'exposition avec des textes de Ryan Rice; Jason Baerg; Lori Blondeau; Martin Loft; Cathy Mattes; Nadia Myre; Ariel Lightningchild Smith.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Presence and Absence Redux: Indian Art in the 1990s - Rice, Ryan (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Les années 1990 sont une décennie cruciale pour l'avancement et le positionnement de l'art et de l'autonomie autochtones dans les récits dominants des états ayant subi la colonisation. Cet article reprend l'exposé des faits de cette période avec des détails fort nécessaires. Pensé comme une historiographie, il propose d'explorer chronologiquement comment les conservateurs et les artistes autochtones, et leurs alliés, ont répondu et réagi à des moments clés des mesures coloniales et les interventions qu'ellesontsuscitéesdu point de vue politique, artistique, muséologique et du commissariat d'expositions. À la lumière du 150e anniversaire de la Confédération canadienne, et quinze ans après la présentation de la communication originale au colloque, Mondialisation et postcolonialisme: Définitions de la culture visuelle v, du Musée d'art contemporain de Montréal, il reste urgent de faire une analyse critique des préoccupations contemporaines plus vastes, relatives à la mise en contexte et à la réconciliation de l'histoire de l'art autochtone sous-représentée.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Déni et ignorance de l'historicité autochtone dans l'histoire de l'art occidentale - Uzel, Jean-Philippe (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Western art history long refused to recognize the historicity of Indigenous art, seeing it instead as a "primitive" mode of human expression. While the dynamism of Indigenous creation since the 1960s has made such an assertion impossible, the institutional recognition given contemporary Indigenous art in the art world is paradoxically accompanied by a lack of critical and theoretical analysis. Today, there is a genuine ignorance concerning Indigenous conceptions of history-their "regime of historicity"-on the part of Western art historians. This is all the more surprising given the recent "temporal turn" taken by the discipline, which emphasizes the question of mixed temporalities without acknowledging it as an essential dimension of Indigenous art. This paper revisits Western art history's long-standing denial of the historicity of Indigenous art, and then considers its current disregard for the ways Indigenous art allows different forms of temporality to coexist. The underlying thesis of the essay is that today's disinterest is, in fact, a prolongation of yesterday's denial.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Art of the Northwest Coast - Jonaitis, Aldona.. (University of Washington Press, 2006)
"Art of the Northwest Coast is a comprehensive survey of the Native arts of the Pacific Northwest Coast, spanning the region from Puget Sound to Alaska, and proceeding from prehistoric times to the present. Incorporating the region's social history with the observations of anthropologists, historians of art, and Native peoples, this rich, vibrant book reveals how a complex web of factors informed these groups' varied responses to the changes and challenges brought about by contact with Europeans."-
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Native Art of the Northwest Coast: A History of Changing Ideas - Townsend-Gault, Charlotte; Kramer, Jennifer (UBC Press, 2013)
This remarkable volume, many years in the making, records and scrutinizes definitions of Northwest Coast Native art and its boundaries. A work of critical historiography, it makes accessible for the first time in one place a broad selection of more than 250 years of writing on Northwest Coast "art." Organized thematically, its excerpted texts are from both published and unpublished sources, some not previously available in English. They cover such complex topics as the clash between oral and written knowledge, transcultural entanglement, the influence of surrealist thinking, and the long history of the deployment of Northwest Coast Native art for nationalist purposes. The selections are preceded by thought-provoking introductions that give historical context to the diverse intellectual traditions that have influenced, stimulated, and opposed each othe
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Unsettling Native Art Histories on the Northwest Coast - Bunn-Marcuse, Kathryn B.; Jonaitis, Aldona (Native art of the Pacific Northwest : a Bill Holm Center series, 2020)
"This edited collection focuses on "unsettling" Northwest Coast art studies, bringing forward voices that uphold Indigenous priorities, engage with past and ongoing effects of settler colonialism, and advocate for practices for more accountable scholarship. Featuring authors with a variety of perspectives, backgrounds, and methodologies, Unsettling Art Histories offers new insights for the field of Northwest Coast art studies. Key themes include discussions of cultural heritage protections and long-standing defenses of natural resources and territory; re-centering women and the critical role they play in transmitting cultural knowledge across generations through materials, techniques, and creations; reflecting on the decolonization work being undertaken in museums; and examining how artworks function beyond previous scholarly framings as living documents carrying information critical to today's inquiries. Re-examining previous scholarship and questioning current institutional practices by prioritizing information gathered in Native communities, the essays in this volume exemplify various methods of "unsettling" and demonstrate how new methods of research have reshaped scholarship and museum practices."
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Afterlives of Indigenous archives: essays in honor of The Occom Circle - Schweitzer, Ivy; Henry, Gordon (Dartmouth College Press, 2019)
"Afterlives of Indigenous Archives offers a compelling critique of Western archives and their use in the development of “digital humanities.” The essays collected here present the work of an international and interdisciplinary group of indigenous scholars; researchers in the field of indigenous studies and early American studies; and librarians, curators, activists, and storytellers. The contributors examine various digital projects and outline their relevance to the lives and interests of tribal people and communities, along with the transformative power that access to online materials affords. The authors aim to empower native people to re-envision the Western archive as a site of community-based practices for cultural preservation, one that can offer indigenous perspectives and new technological applications for the imaginative reconstruction of the tribal past, the repatriation of the tribal memories, and a powerful vision for an indigenous future."
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Art for a New Understanding: Native Voices, 1950s to Now - Hopkins, Candice; Well-Off-Man, Manuela; Besaw, Mindy N.; Crystal Bridges Museum of American Art (University of Arkansas Press, 2018)
"Art for a New Understanding, an exhibition from Crystal Bridges Museum of American Art that opened in October 2018, seeks to radically expand and reposition the narrative of American art since 1950 by charting a history of the development of contemporary Indigenous art from the United States and Canada, beginning when artists moved from more regionally-based conversations and practices to national and international contemporary art contexts. This accompanying book documents and expands on the histories and themes of this exciting exhibition. This fully illustrated volume includes essays by art historians and historians and reflections by the artists included in the collection. Also included are key contemporary writings--from the 1950s onward--by artists, scholars, and critics, investigating the themes of transculturalism and pan-Indian identity, traditional practices conducted in radically new ways, displacement, forced migration, shadow histories, the role of personal mythologies as a means to reimagine the future, and much more. As both a survey of the development of Indigenous art from the 1950s to the present and a consideration of Native artists within contemporary art more broadly, Art for a New Understanding expands the definition of American art and sets the tone for future considerations of the subject. It is an essential publication for any institution or individual with an interest in contemporary Native American art, and an invaluable resource in ongoing scholarly considerations of the American contemporary art landscape at large."
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

The Early Years of Native American Art History: The Politics of Scholarship and Collecting - Berlo, Janet Catherine (ACLS Humanities E-Book, 1992)
This collection of essays deals with the development of Native American art history as a discipline.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Amérique du Nord: arts premiers - Berlo, Janet Catherine; Phillips, Ruth B. (Terre indienne, 2006)
Replaçant chaque oeuvre dans son contexte familial, social, géographique, économique et spirituel, cet album présente l'art des peuples premiers d'Amérique du Nord, des Inuits aux peuples des déserts du sud-ouest des Etats-Unis, des origines à la période contemporaine
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

La crise d'Oka en récits: territoire, cinéma et littérature - St-Amand, Isabelle (Collection InterCulture, 2015)
La crise d'Oka marque un véritable moment de rupture dans lesrelatlons entre les premiers peuples et les colonies de peuplement. Dans les suites immédiates de l’échec de l’accord du lac Meech, ce long siège armé de 78 jours rend visible une présence autochtone que les sociétés québécoise et canadienne avaient imaginée évanouie. Àl’inverse, l’opposition à l’empiétement mis en œuvre à Kanehsatàke età Kahnawàke réactive une longue histolre de résistance au projet colonial d'appropriation des terres et d'effacement des peuples autochtones. Ce livre envisage la crise d'Oka, ou la résistance à Kanehsatàke, comme un espace de focalisatlon où se donne à voir larelation globale entre les peuples. Qu'est-ce que l'événement fait surgir, transforme et crée, dans la scénographie du siège, mais aussi dans les films documentaires et les récits littéraires, autochtones et allochtones? À l'heure où une nouvelle génération revient sur cette crise politique aux enjeux non résolus, ce livre ouvre un espace où entrent en relation et s'affrontent différents intérêts, connaissances et expressions relatifs à ce conflit territorial. Il engage une réflexion épistémologique essentielle à un processus de décolonisation aussi impératif qu'exigeant.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Repenser le temps et l'espace, du wampum au selfie - Vigneault, Louise (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
This article considers the way certain Indigenous artists are reviving conceptions of territory and history that are anchored in secular epistemologies and the construction of knowledge. Such conceptions provide a way for these artists to respond to colonial appropriation, reactivate interrupted dialogues, engender new forms of territorialization, and create places of commemoration and memory preservation. Similar to the historiographical deconstruction performed by thinkers and activists such as Vine Deloria Jr. and Taiaiake Alfred, these artists’ works offer a model of autonomy and environmental balance. While some are reviving mnemonic practices, such as the making of wampum, which traditionally preserve memories of alliances and conflicts, others have embraced Internet and selfie technologies as a means of creating new spaces for speech and recognition
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Imagining Indigenous Digital Futures: An Afterword - Raheja, Michelle (Studies in American Indian Literatures, 2017)
In lieu of an abstract, here is a brief excerpt of the content: As I sit writing in my kitchen while the forces of the U.S. military state are brought to bear on thousands of Standing Rock water stewards and land protectors and their allies in Cannonball, North Dakota, I consider how this sail special issue on digital Indigenous studies not only represents a collection of essays about the critical work Indigenous women are performing in their various digital projects but also illustrates that these online “Indigenous territories” (Hearne), crafted on social media platforms such as Twitter and Facebook, save lives. Every single day since the protectors first gathered to oppose the proposed 1,170-mile Dakota Access pipeline (a project that would potentially contaminate the Missouri watershed and the Ogallala Aquifer and desecrate Dakota sacred sites), digital independent and social media have constantly covered the story. At least 1.3 million Facebook users checked in virtually at Oceti Sakowin and other Indigenous camps and communities to ensure that support presence is recognized, while the world monitors the presence of the military and police force gathering at the construction site to curb further violence. The Standing Rock gathering offers hope to networked Indigenous youth, a demographic between three and ten times as likely to commit suicide than the national average peer rate. The Nodapl action in the Indigenous imaginary is an invitation to stand at the front lines of a global movement to protect water and land resources for all living beings on this planet and to draw attention to and support those whose lives and ways of being are in peril through overt military action and consequential environmental destruction. It is also an occasion, in the words of Jolene Rickard, “to invest in the apparatus of the imagination” (Bernardin). One need only look at the online art, handwritten signs, and logos representing #nodapl, #standingrock, [End Page 172] #waterislife, and #rezpectourwater to see the ways in which Indigenous artists are creatively and powerfully envisioning this movement, most often immersed with work that features strong images of Native women and girls, the community backbone and life force. Or we need only view digital videos like computer animator and artist Joseph Erb’s black-and-red graphic history of Standing Rock, “Mni Wiconi / Water Is Life” (https://www.youtube.com/watch?v=kXoy5lzpjiM), and first-person game platforms like Elizabeth LaPensée’s Thunderbird Strike, which extend the conversations at Standing Rock to the struggles over Enbridge’s Alberta tar sands pipeline and fracking practices as players work to undo and prevent further environmental degradation. Following Idle No More’s digital and geospatial (re)articulation of Indigenous territories, we are now living and loving and hoping in this historic moment as new ways of relating to one another and living in deep connection with the land and all its forms of life are being physiologically, intellectually, and spiritually forged at the geospatial confluence of the Missouri and Cannonball Rivers. They are being forged as well through the confluences of digital rivers on our electronic devices and in our online conversations about the beauty and devastation of the events that are unfolding in Standing Rock. Susan Bernardin’s essay in this issue on Heid E. Erdrich’s “Pre-Occupied” considers the meaning of rivers to Native peoples and contends that images of waterways, particularly the Mississippi, are mobilized “to make visible the continuing claims of this and other imperiled riverine systems.” In her introduction, Joanna Hearne asks us, “How might such an intersection of digital and Indigenous specificities take place in a way that is ‘native to the device’; that is, how might Indigenous specificity be embedded in shared platforms that are therefore central to all of our digital lives?” The essays in this special issue respond to this question by theorizing digital media in fresh and innovative ways. Many of us teach digital humanities courses or classes with strong digital media content, but we lack the language for critically engaging this new field on its own terms as it intersects, extends, and radically reconceptualizes more familiar research areas such as cinema studies, Indigenous / Native American studies, communication, literature, art, and history.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

When Rivers Were Trails: Cultural Expression in an Indigenous Video Game - LaPensée, Elizabeth (International Journal of Heritage Studies, 2021)
When Rivers Were Trails is a 2D adventure game wherein The Oregon Trail meets Where the Water Tastes Like Wine through an Indigenous lens. The game depicts a myriad of cultures during the player’s journey from Minnesota to California amidst the impact of land allotment in the 1890s. Initiated by the Indian Land Tenure Foundation, the game was developed in collaboration with the Games for Entertainment and Learning Lab at Michigan State University thanks to support from the San Manuel Band of Mission Indians and the many Indigenous creatives who contributed design, art, music, and writing. Uniquely, When Rivers Were Trails is a sovereign game, meaning that it was directed and informed by Indigenous creatives who maintained the role of final decisions during development. Merging design research and close reading methods, this study sets out to describe the game’s design, development process in regards to the game writing, and the resulting themes which emerged as a result of engaging Indigenous writers in self-determined representations.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Gaming Representation: Race, Gender, and Sexuality in Video Games - Malkowski, Jennifer; Russworm, TreaAndrea M. (Indiana University Press, 2017)
Gaming Representation' offers a timely and interdisciplinary call for greater inclusivity in video games. The issue of equality transcends the current focus in the field of Game Studies on code, materiality, and platforms. Journalists and bloggers have begun to hold the digital game industry and culture accountable for the discrimination routinely endured by female gamers, queer gamers, and gamers of color. Video game developers are responding to these critiques, but scholarly discussion of representation in games has lagged behind. Contributors to this volume examine portrayals of race, gender, and sexuality in a range of games, from casuals like Diner Dash, to indies like Journey and The Binding of Isaac, to mainstream games from the Grand Theft Auto, BioShock, Spec Ops, The Last of Us, and Max Payne franchises. Arguing that representation and identity function as systems in games that share a stronger connection to code and platforms than it may first appear, 'Gaming Representation' pushes gaming scholarship to new levels of inquiry, theorizing, and imagination.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créatrice; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Critical media studies, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

A Pedestal, A Table, A Love Letter: Archaeologies of Gender in Videogame History - Nooney, Laine (Game Studies, 2013)
The history of videogames has largely been imagined as a patrilineal timeline. Women, when they emerge as participants in the game industry, are typically figured as outliers, exceptions, or early exemplars of “diversity” in the game industry. Yet the common practice of “adding women on” to game history in a gesture of inclusiveness fails to critically inquire into the ways gender is an infrastructure that profoundly affects who has access to what kinds of historical possibilities at a specific moment in time and space. This contribution aims to shift the relevant question from “Where are women in game history?” to “Why are they there in the way that they are?” To do so, the essay strategically deploys Sierra On-Line co-founder and lead designer Roberta Williams as an exceptional case study on the problem of gender in videogame history. Drawing from both media archaeology and feminist cultural studies, this contribution first outlines the function Roberta Williams serves as a gendered subject of game history. The remainder of the essay is organized as three short, non-chronological vignettes about specific objects and practices in the biography of Roberta Williams. Attention to the contextual specificity of Roberta Williams and her historical moment produces an alternative genealogy for gaming centered around relations of intimacy and labor in domestic space. Rather than producing a chronology, the method of this essay illustrates a historical critique by sketching a contour that unsettles the presumptive logic of what we must account for when we write about the objects and subjects of game history.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé

Exposer, diffuser, faire entendre sa voix: présence de l'art contemporain autochtone au Québec entre 1967 et 2013 - De Lacroix, Pricile (Université du Québec à Montréal, 2017)
Ce mémoire se penche sur la diffusion de l'art contemporain autochtone au Québec de 1967 à 2013. Grâce à un corpus constitué de 640 expositions comprenant au moins un artiste des Premières Nations, métis ou inuit s'étant tenues quelque part dans la province à l'intérieur de ces 46 années, il a été possible de dresser un portrait global raisonné de ce qui s'est fait – ou ne s'est pas fait – concrètement, au-delà des a priori maintes fois reconduits. Il démontre, par exemple, que la décennie 1990 n'a pas été si « désertique » qu'il n'y parait, mais que la période 2000-2013, malgré son apparente vigueur, cache plusieurs dynamiques à l'œuvre au Québec rendant la reconnaissance et l'intégration des artistes autochtones dans le grand réseau des arts contemporains encore difficile. Ce mémoire apporte un éclairage sur le rôle marquant joué par les réseaux parallèles dans la diffusion de l'art contemporain autochtone, celui, parfois novateur, joué par les musées d'histoire et d'ethnographie ainsi que par les musées au sein même des communautés autochtones, puis la fermeture bien visible des institutions d'art du Québec jusqu'au milieu des années 2000. Il met également en lumière la présence de solitudes existantes au Québec, c'est-à-dire celle qui opère une division entre les artistes autochtones francophones et anglophones, favorisant grandement ces derniers, ainsi qu'entre artistes autochtones versus allochtones, les deux se mélangeant encore difficilement au sein des expositions. Enfin, ce mémoire permet de constater qu'en quatre décennies, le nombre d'artistes autochtones pratiquant de manière professionnelle au Québec n'a cessé d'augmenter, que Montréal s'est inscrite de plus en plus comme une métropole pouvant attirer des artistes autochtones de calibre national et international, que certaines régions du Québec, comme le Saguenay et l'Abitibi, ont, contrairement à d'autres, fait preuve d'une ouverture certaine face à l'art autochtone, mais également qu'il y a eu – et qu'il y a peut-être encore – une corrélation entre événements festifs et expositions accrues d'art contemporain autochtone, ce qui a tendance à le garder dans le domaine du folklore au Québec, et nuire véritablement à la reconnaissance des artistes professionnels.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

“I Want to Call Their Names in Resistance”: Writing Aboriginal Women into Canadian Art History. - Farrell Racette, Sherry (Rethinking Professionalism: Essays on Women and Art in Canada, 1850-1970, 2012)
As bell hooks points out in “Aesthetic Inheritances: History Worked by Hand,” writing an inclusive art history is no easy task. Until very recently, Aboriginal women have been written out of Canadian art history, or rather art history has been written around us. How do we write ourselves in? It falls far beyond simple insertion; the erasures are far too deep. Insertion presumes a simple forgetfulness, an oversight, a neglecting of the obvious. Insertion assumes a presence. It implies a shared mode of history, a common belonging to a collective archive, and an agreed-upon understanding of what it means to be an artist. Beyond the important considerations of race, gender, culture, and social class, our distinct legal status in Canada must be acknowledged. This was particularly true for women artists working between 1880 and 1970. For much of the time period under consideration, First Nations communities lived under a profoundly restrictive regime of colonial power. Relationships between First Nations people and the Canadian state have been defined by the Indian Act, a piece of legislation enacted in 1876 and surviving, through many amendments and revisions, until the present time.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Close Encounters: The Next 500 Years - Farrell Racette, Sherry. (Plug In Editions., 2011)
Catalogue d'exposition publié à l'occasion de l'exposition tenue au Plug In Institute of Contemporary Art, Urban Shaman Contemporary Aboriginal Art, et Winnipeg Art Gallery, du 22 janvier au 8 mai 2011. Now is the moment to reconfigure our notions of time to reveal alternative ways of thinking and being for the future. In Close Encounters: The Next 500 Years Indigenous artists imagine the future within the context of present experiences and past histories. By radically reconsidering encounter narratives between native and non-native people, Indigenous prophecies, possible utopias and apocalypses, this exhibition proposes intriguing possibilities for the next 500 years. "We all in different measure have carved out the future," observes Hopi photographer and filmmaker, Victor Masayesva, in his book Husk of Time. "We are all clairvoyants, soothsayers, prophets, knowingly assuming our predictions. Close Encounters brings together over 30 Indigenous artists from across Canada, the United States, South America, Europe, Australia and New Zealand, including newly commissioned work from Rebecca Belmore, Faye HeavyShield, Kent Monkman, and Edward Poitras. Jimmie Durham's sculptural work A Pole to Mark the Centre of the World (at Winnipeg) will be an ongoing critique of widely held ideas surrounding space and location, while James Luna's poignant installation The Spirits of Virtue and Evil Await my Ascension, addresses issues of ritual and the passing of time. Close Encounters showcases artists and artworks that collectively invent provocative futures from a diversity of perspectives and practices. With its myriad histories, trajectories, tensions, collisions, and self-image(s), the city of Winnipeg offers an intriguing juxtaposition for these artistic mediations. Close Encounters: The Next 500 Years presents international Indigenous perspectives in a city that in many ways also epitomizes the future of Aboriginal people in Canada. Works in multiple venues throughout the city will serve as catalysts to invent different ways of thinking, acting, and being in the world of our shared future. At this pivotal moment in time, Close Encounters invites engagement with the speculative, the prophetic, and the unknown
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé